Person and Social Deixis in Shamsi’s Islamic Preaching to an Atheist - Robinda; Fitri Rakhmawati (Universitas Islam Negeri Palopo, 2025)
This study examines the use of person and social deixis in Shamsi’s preaching, a Muslim preacher, in Islamic dawah through debate with an atheist at Speaker’s Corner in Hyde Park, London. Using Levinson’s (1983) theory of deixis, the research identifies the types and expressions of deictic language used by the preacher when engaging with a non-believer. The data were taken from the DUS Dawah YouTube channel, specifically from a video titled “An Atheist Thinks It's Okay to Sleep with a Baby”. The analysis adopts a descriptive qualitative method. The finding shows that Shamsi uses all types of person deixis. The most dominant is the second person “you”, which appears 118 times, followed by the first person “I” used 21 times, and third person forms such as “he” and “someone”, each used 6 times. In terms of social deixis, Shamsi employs two categories. In the first category, relational social deixis, the most frequently used form is the referent honorific “Prophet” (9 times). This is followed by formality level expressions, such as “the scholar(s)”, which appear 4 times, and audience honorifics like “everyone”, used 1 time. Meanwhile, addressee honorifics do not appear in Shamsi’s preaching, indicating that this form of honorifics was not used in the interaction. In the second category, absolute social deixis, Shamsi refers to himself with the phrase “I'm Muslim” (1 time) as an authorized speaker, and refers to his opponent with the phrase “as an atheist” (1 time) as an authorized recipient. Overall, both person and social deixis used by Shamsi, functioned as powerful linguistic tools to engage intimacy and effectively convey his Islamic message, by defining identity, asserting authority, emphasizing ideological differences to an atheist in public space.